Assessment of inpatient multimodal cardiac imaging appropriateness at large academic medical centers. Issue 1 (December 2015) - Remfry, Andrew; Abrams, Howard; Dudzinski, David; Weiner, Rory; Bhatia, R.
Abstract Background Responding to concerns regarding the growth of cardiac testing, the American College of Cardiology Foundation (ACCF) published Appropriate Use Criteria (AUC) for various cardiac imaging modalities. Single modality cardiac imaging appropriateness has been reported but there have been no studies assessing the appropriateness of multiple imaging modalities in an inpatient environment. Methods A retrospective study of the appropriateness of cardiac tests ordered by the inpatient General Internal Medicine (GIM) and Cardiology services at three Canadian academic hospitals was conducted over two one-month periods. Cardiac tests characterized were transthoracic echocardiography (TTE), transesophageal echocardiography (TEE), single-photon emission tomography myocardial perfusion imaging (SPECT), and diagnostic cardiac catheterization. Results Overall, 553 tests were assessed, of which 99.8 % were classifiable by AUC. 91 % of all studies were categorized as appropriate, 4 % may be appropriate and 5 % were rarely appropriate. There were high rates of appropriate use of all modalities by GIM and Cardiology throughout. Significantly more appropriate diagnostic catheterizations were ordered by Cardiology than GIM (93 % vs. 82 %, p  = <0.01). Cardiology ordered more appropriate studies overall (94 % vs. 88 %, p  = 0.03) but there was no difference in the rate of rarely appropriate studies (3 % vs. 6 %, p  = 0.23). Conclusion The ACCF AUC captured the vast majority of clinical scenarios for multiple cardiac imaging modalities in this multi-centered study on Cardiology and GIM inpatients in the acute care setting. The rate of appropriate ordering was high across all imaging modalities. We recommend further work towards improving appropriate utilization of cardiac imaging resources focus on the out-patient setting.